Indoor air quality and the associated health risk in primary school buildings in Central Europe - The InAirQ study - Szabados, Máté; Csákó, Zsófia; Kotlík, Bohumil; Kazmarová, Helena; Kozajda, Anna; Jutraz, Anja; Kukec, Andreja; Otorepec, Peter; Dongiovanni, Arianna; Di Maggio, Andrea; Fraire, Stefano; Szigeti, Tamás (Indoor air, 2021)
The indoor air quality (IAQ) was investigated in sixty-four primary school buildings in five Central European countries (Czech Republic, Hungary, Italy, Poland, and Slovenia). The concentration of volatile organic compounds, aldehydes, PM2.5 mass, carbon dioxide, radon, as well as physical parameters were investigated during the heating period of 2017/2018. Significant differences were identified for the majority of the investigated IAQ parameters across the countries. The median indoor/outdoor ratios varied considerably. A comprehensive evaluation of IAQ in terms of potential health effects and comfort perception was performed. Hazard quotient values were below the threshold value of 1 with one exception. In contrast, 31% of the school buildings were characterized by hazard index values higher than 1. The maximum cumulative ratio approach highlighted that the concern for non-carcinogenic health effects was either low or the health risk was driven by more substances. The median excess lifetime cancer risk values exceeded the acceptable value of 1 × 10-6 in the case of radon and formaldehyde. PM2.5 mass concentration values exceeded the 24 h and annual guideline values set by the World Health Organization in 56 and 85% of the cases, respectively. About 80% of the schools could not manage to comply with the recommended concentration value for carbon dioxide (1000 ppm).
Keywords: indoor air; látky znečišťující vzduch; Evropa; Europe; Environmental Monitoring; Schools; InAirQ; školy; health risk assessment; znečištění vzduchu ve vnitřním prostředí; Air Pollution, Indoor; monitorování životního prostředí; monitoring campaign; environmental health; children; Air Pollutants